Environmental impact and occupational risk in gasification plants processing residues of sewage sludge and refuse-derived fuel: a review - Alves, Octávio (2019)
The authors acknowledge financial support provided by Fundação para a Ciência e Tecnologia from Ministério da Ciência, Tecnologia e Ensino Superior (grant no. SFRH/BD/111956/2015), cofinanced by Programa Operacional Potencial Humano and União Europeia-Fundo Social Europeu.